Biodiversity of Amarumatena Tourism Hamlet: Potential for Local Wisdom-Based Educational Tourism on Ambon Island - Merlin Renny Sitanala; Yosevita Latupapua; Ronny Loppies (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aims to identify the diversity of flora and fauna and to analyze their potential use as educational tourism attractions based on local wisdom that support conservation and environmental education. The study employed a mixed-methods approach with an exploratory-descriptive design. Biodiversity data were obtained through vegetation inventories and fauna observations, while social data were collected through semi-structured interviews. The results showed that Amarumatena Tourism Hamlet possesses high biodiversity, consisting of 51 species of family medicinal plants (Tanaman Obat Keluarga [TOGA]), 27 ornamental plant species, 14 multipurpose tree species (MPTS), and 10 food crop species, as well as fauna belonging to the bird, herpetofauna, and invertebrate groups. This biodiversity functions not only as a visual attraction but also as an educational medium for ethnobotany, conservation, and local food security. The integration of biodiversity with local wisdom practices, such as the dusung system and sago processing, indicates that this landscape serves as a community-based ecological learning space. Theoretically, this study contributes to enriching the concept of educational tourism by integrating biodiversity and local wisdom within the context of traditional agroforestry. Practically, it offers a conceptual framework for the development of dusung-based educational tourism that can be applied in island regions.